2003
DOI: 10.1002/immu.200310022
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional characterization of the interaction between pentraxin 3 and C1q

Abstract: Pentraxin 3 (PTX3) is a recently characterized member of the pentraxin family of acute-phase proteins produced during inflammation. Classical short pentraxins, C-reactive protein, and serum amyloid P component can bind to C1q and thereby activate the classical complement pathway. Since PTX3 can also bind C1q, the present study was designed to define the interaction between PTX3 and C1q and to examine the functional consequences of this interaction. A dose-dependent binding of both C1q and the C1 complex to PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
269
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 320 publications
(283 citation statements)
references
References 39 publications
10
269
0
4
Order By: Relevance
“…Not only CRP but also PTX3, another member of the pentraxin family, was recently shown to interact with the globular head of C1q (19). Furthermore, competition studies strongly suggested that PTX3, CRP and the pentraxin family member SAP recognize the same domain of C1q (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only CRP but also PTX3, another member of the pentraxin family, was recently shown to interact with the globular head of C1q (19). Furthermore, competition studies strongly suggested that PTX3, CRP and the pentraxin family member SAP recognize the same domain of C1q (19).…”
Section: Discussionmentioning
confidence: 99%
“…The following anti-C1q mAbs were used: anti-C1q-2, -42, -52, -85, -89, -124, -130, -171 (also known as mAb 2204; Ref. 19) and anti-C1q-193. F(abЈ) 2 were prepared by incubation of each mAb with pepsin (Sigma-Aldrich) with a mAb-pepsin ratio of 40:1 w/w, in 0.1 M sodium citrate (pH 3.5), at 37°C for 20 h. The reaction was stopped by adding 1 M Tris to adjust the pH to 8.5.…”
Section: Monoclonal Absmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of PTX3 ligands have been described so far, suggesting different physiological and/or pathological roles for this protein. PTX3 binds with high affinity to the complement component C1q thus activating the complement system through the classical pathway (10,11). The selective recognition of fibroblast growth factor-2 (FGF-2) by PTX3 inhibits FGF-2 angiogenic activity on endothelial cells (12) and blocks the autocrine and paracrine stimulation exerted by FGF-2 on smooth muscle cells (13).…”
mentioning
confidence: 99%
“…PTX3 is a member of the superfamily of pentraxins and plays a part in acute inflammatory reactions caused by trauma or infection. PTX3, differently from most other molecules, is produced by many cells, such as macrophages, dendritic cells, fibroblasts and activated endothelial cells, at the inflammatory site [81][82][83]. These cells produce and release PTX3 when stimulated by inflammatory mediators such as lipopolysaccharide, IL-1 and TNF-α, which induce the NFκB promoter which is associated with the gene for PTX3 [81,82].…”
Section: Pentraxinmentioning
confidence: 99%